1998
DOI: 10.1139/f98-063
|View full text |Cite
|
Sign up to set email alerts
|

DNA and allozyme markers provide concordant estimates of population differentiation: analyses of U.S. and Canadian populations of Yukon River fall-run chum salmon (Oncorhynchus keta)

Abstract: Although the number of genetic markers available for fisheries research has steadily increased in recent years, there is limited information on their relative utility. In this study, we compared the preformance of different "classes" of genetic markers (mitochondrial DNA (mtDNA), nuclear DNA (nDNA), and allozymes) in terms of estimating levels and partitioning of genetic variation and of the relative accuracy and precision in estimating population allocations to mixed-stock fisheries. Individuals from eight po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 23 publications
4
55
1
Order By: Relevance
“…Mean F ST (0.057) showed that 94.3% of the genetic divergence was within chum salmon populations and only 5.7% was due to the divergence among populations, which is in agreement with the breeding habit of chum salmon. F ST averaged over all loci in this study (0.057) is comparable with chum salmon from the southern Russian Far East (0.052) (Efremov et al 2001) and the Yukon River (0.030) (Scribner et al 1998) and the Yukon River, Alaska (0.021) (Olsen et al 2004). Genetic divergence among populations in China is higher than that of the Yukon River populations.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Mean F ST (0.057) showed that 94.3% of the genetic divergence was within chum salmon populations and only 5.7% was due to the divergence among populations, which is in agreement with the breeding habit of chum salmon. F ST averaged over all loci in this study (0.057) is comparable with chum salmon from the southern Russian Far East (0.052) (Efremov et al 2001) and the Yukon River (0.030) (Scribner et al 1998) and the Yukon River, Alaska (0.021) (Olsen et al 2004). Genetic divergence among populations in China is higher than that of the Yukon River populations.…”
Section: Discussionsupporting
confidence: 72%
“…However, in our study of chum salmon populations in China, the mean observed heterozygosity (Ho) of four loci (Oke3, Oke4, Oke8 and Oke11) were 0.64, 0.50, 0.75 and 0.45, respectively. Total gene diversity (Ht) (Nei 1973) across the four populations was 0.676, but it was 0.592 in the Yukon River according to microsatellite analysis (Scribner et al 1998). This implies a high level of genetic diversity in Chinese chum salmon populations.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the direction and magnitude of differentiation at mtDNA relative to the nuclear DNA markers is very close to that predicted assuming selective neutrality. Several recent studies with salmonid fishes also have found similar patterns of differentiation at allozymes and nuclear DNA markers (Sánchez et al 1996;Estoup et al 1998;Scribner et al 1998).…”
Section: Discussionmentioning
confidence: 59%
“…Oncorhynchus keta Scribner et al 1998 VNTRs ϭ introns ϭ proteins water buffalo Bubalus bubalis Barker et al 1997 VNTRs ϭ proteins blue marlin Makaira nigricans Buonaccorsi et al 1999 …”
Section: Discussionmentioning
confidence: 99%
“…This can be accomplished using a genotyping tool that can identify each stock within the 84 lake. Multiple marker systems are often used to identify stocks in fish populations (Beacham et al, 2004;Beacham et al, 2005) and can offer a greater amount of precision in estimating population origins in mixed stock fisheries (Scribner et al, 1998). Most studies used a combination of Mhc variation and microsatellites.…”
Section: Resultsmentioning
confidence: 99%